Exploring the Impact of Mobile Apps on English Vocabulary Learning Intentions Among Gen X Adults Learners in Chengdu, China - Wang, Zhenzhen (Scholar: Human Sciences, 2025)
Purpose: The purpose of this study is to investigate the impact of Gen X users in Chengdu, China, on their English learning behavior intention by using the most popular English word learning Applications in China among system quality, information quality, service quality, perceived usefulness, attitude, technology characteristics, task characteristics, task-technology fit and behavior intention. Research design, data, and methodology: The researchers conducted the study based on quantitative research methods. The data were collected from 500 Gen X living in Chengdu who have used the top three English word-learning Applications in China to learn English. This study focuses on confirmatory factor analysis and structural equation modeling as statistical tools to test data, model accuracy, and key variables' influence. Results: The results show that behavioral intention has the most influence on the use attitude. In addition, system quality, information quality, service quality, attitude, technical characteristics, task characteristics, and personal perception are statistically significant and impact the behavioral intention. Nevertheless, technology characteristics has no significant impact on task-technology fit. Conclusions: Developers and educators can create more engaging, effective, and user-friendly English word learning applications that cater to the needs of Gen X users in Chengdu, China, which does not only enhance user satisfaction but also improve learning outcomes and foster a more positive attitude towards using mobile applications for language learning.